Determinants of Outcome of Neonates Admitted in the University College Hospital (UCH) Ibadan, Oyo State, Nigeria (2018)
Neonatal period is a crucial period compared to any other time during infancy as they are at high risk of dying during this period. The Neonatal Intensive Care Unit (NICU) of UCH is a highly technical specialized unit in the hospital that provides medical/nursing care to sick and/or high-risk premature infants. Yet some babies admitted to this unit fail to survive. The aim of this study is to determine characteristics of neonates admitted at NICU and factors influencing outcome of care. A retrospective descriptive survey based on case record of babies admitted for a five year period between January 2007 and December 2011. Check list was used for data collection of the 1020 neonates admitted during the period. Analysis was done using statistical package for social sciences (SPSS) version 17 software. Out of the 1020 neonates, male babies were more 549(53.8%) than their female counterparts 468 (45.9%). Most 992(97.3%) of their mothers were not booked or registered for antenatal care and were not referred early to UCH causing the babies to be in fetal distress before arrival to the hospital. Mortality was less (16.6%) among the in-born than out-born babies (35.8%). It was observed that male neonates, preterm/low birth weight and their time of admission were associated with poor outcome. There is a significant association between mothers' occupation, pregnancy complication, place of birth, mode of delivery and neonates care outcomes (p<0.05). Binary logistic regression analysis shows that mothers who had up to tertiary (university) level of education are three times more likely to have babies who survived and discharged home alive compared to those who had no formal education. There is need for nurses to educate women on the importance of early antenatal booking and delivery in a well-equipped facility. Prompt screening, identification and referral of women at risk and prompt resuscitation of new-born with asphyxia should be ensured.